Additive manufacturing metal powder and methods of making and using the same

CN122428192BActive Publication Date: 2026-10-23TEPUCHUANG LASER TECHNOLOGY (HANGZHOU) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610895172.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-23
Estimated Expiration
2046-06-22

AI Technical Summary

Technical Problem

[0003]目前,铝合金压铸模具主要采用H13、1.2344、M308等传统模具钢,通过机加工、热处理制成,但传统模具钢存在两大核心缺陷:一是导热性能较差,导热率通常低于50W/(m·K),导致压铸过程中模具内部热量无法快速散发,模具温度分布不均,易产生热应力集中,引发模具开裂、变形,同时延长了压铸产品冷却时间,降低生产效率;二是传统机加工工艺难以制备复杂结构压铸模(如随形冷却流道、异形型腔),无法实现模具结构优化,进一步限制了散热效率和生产效率的提升

Benefits of technology

[0028]本申请所述的增材制造金属粉末,通过在W-Ni-Cu体系中引入了微量Nb元素,同时优化Cu含量至21.0%,并添加特定含量的Co、Mo,形成W-Ni-Cu-Co-Mo-Nb多元成分体系,经激光选区熔化打印构建W弥散强化、Nb-Mo固溶强化及Co晶界强化的多元协同强化机制,在有效提升合金件导热性能的同时,优化打印适配性,提升耐磨及抗冲蚀能力,使合金件的综合性能协同提升,显著延长使用寿命,突破了现有3D打印合金件的导热、耐磨、打印性能三者无法协同提升的技术瓶颈,尤其克服了传统铝合金压铸模具材料导热差、耐磨不足及SLM打印易开裂的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122428192B_ABST
    Figure CN122428192B_ABST
Patent Text Reader

Abstract

The application relates to an additive manufacturing metal powder and a preparation method and application thereof, wherein the components of the additive manufacturing metal powder, in terms of mass fraction, comprise W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5% and impurities, and the total content of the impurities is less than or equal to 0.5%; the additive manufacturing metal powder is printed by laser selective melting to form an alloy phase in which W dispersion strengthening particles are distributed, and the alloy grain size is 3.6 mu m. The additive manufacturing metal powder provided by the application has excellent heat conduction performance, wear resistance and SLM printing performance, can be adapted to SLM printing of an aluminum alloy die casting die, and is especially suitable for high-end aluminum alloy die casting industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of additive manufacturing materials technology, and in particular to an additive manufacturing metal powder, its preparation method, and its application. Background Technology

[0002] Aluminum alloy die casting molds are the core components in aluminum alloy die casting production. Their working environment is harsh, and they need to withstand the scouring of molten aluminum alloy (600℃~700℃), high-temperature oxidation, repeated thermal shock and large mechanical stress for a long time. Therefore, there are extremely high requirements for the thermal conductivity, wear resistance, high temperature stability, thermal fatigue resistance and laser selective melting (SLM) printing compatibility of the material.

[0003] Currently, aluminum alloy die casting molds mainly use traditional mold steels such as H13, 1.2344, and M308, which are manufactured through machining and heat treatment. However, traditional mold steels have two major defects: First, they have poor thermal conductivity, typically below 50 W / (m·K), which prevents the heat inside the mold from dissipating quickly during the die casting process. This results in uneven temperature distribution in the mold, which easily leads to thermal stress concentration, causing mold cracking and deformation. It also prolongs the cooling time of the die-cast products and reduces production efficiency. Second, traditional machining processes are difficult to use to manufacture complex die casting mold structures (such as conformal cooling channels and irregular cavities), making it impossible to optimize the mold structure and further limiting the improvement of heat dissipation efficiency and production efficiency.

[0004] With the development of SLM metal 3D printing technology, it is possible to achieve near-net-shape forming of complex structures, providing a possibility for the structural optimization of aluminum alloy die-casting molds. However, existing die-casting mold alloy materials suitable for SLM printing still have obvious technical shortcomings: conventional nickel-tungsten-copper-based alloys have a thermal conductivity of less than 80 W / (m·K), which cannot meet the requirements for efficient heat dissipation; some alloys increase the content of high-melting-point elements to improve wear resistance, resulting in increased alloy brittleness, and defects such as incomplete fusion and hot cracking are prone to occur during SLM printing; at the same time, existing alloy materials cannot balance thermal conductivity, wear resistance and SLM printing performance, and cannot be adapted to the harsh working environment of aluminum alloy die-casting molds, limiting their application in the high-end aluminum alloy die-casting industry. Summary of the Invention

[0005] Based on this, it is necessary to provide an additive manufacturing metal powder, its preparation method, and its application to address the above-mentioned problems. The additive manufacturing metal powder provided in this application has excellent thermal conductivity, wear resistance, and SLM printing performance, and can be adapted to SLM printing of aluminum alloy die casting molds, especially suitable for the high-end aluminum alloy die casting industry.

[0006] An additive manufacturing metal powder, by mass fraction, comprises: W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5%, and impurities, wherein the total impurity content is ≤0.5%.

[0007] The alloy phase formed by selective laser melting and printing of the additive manufacturing metal powder contains W-dispersed reinforcing particles, and the alloy grain size is 3.6 μm.

[0008] The preparation steps of the additive manufacturing metal powder are as follows:

[0009] (1) Ingredients: Select W powder, Ni powder, Cu powder, Co powder, Mo powder and Nb powder with a purity of 99.95% and a particle size of ≤8μm. Weigh them accurately according to the following ratios: W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5%, and unavoidable impurities ≤0.5%. The ingredient error is ≤±0.1%.

[0010] (2) Graded mixing: The raw material powder is placed in a high-purity argon-protected powder mixer. First, it is mixed at a low speed of 180 r / min for 2 hours, and then at a high speed of 300 r / min for 3.5 hours. The powder is cooled at a 15-minute interval in between to obtain a uniformly mixed powder.

[0011] (3) Melting and atomization: The mixed powder is added to a vacuum induction melting furnace and heated to 1580°C under the protection of high-purity argon gas. After complete melting, a uniform alloy melt is obtained. Secondary high-pressure argon gas atomization is used. The first atomization pressure is 4.0 MPa and the second atomization pressure is 5.2 MPa. The atomization temperature is 1530°C to obtain the initial powder.

[0012] (4) Sieving and drying: Two-stage sieves of 45μm and 18μm were used to screen out powder of 18μm~42μm; magnetic impurities were removed by magnetic separation, non-metallic inclusions were removed by ultrasonic cleaning, and vacuum drying was performed at 90℃ for 3h.

[0013] (5) Packaging: Place the prepared powder into a vacuum packaging bag, evacuate to 8 Pa, and seal for storage.

[0014] In one embodiment, the additively manufactured metal powder satisfies the following condition:

[0015] (1) The sphericity of the additively manufactured metal powder is 97%;

[0016] (2) The oxygen content of the additive manufacturing metal powder is 320 ppm;

[0017] (3) In the additive manufacturing metal powder, the mass of particles with a particle size of 18μm~30μm accounts for 55% of the total mass of the powder;

[0018] (4) The flowability of the additively manufactured metal powder is 20s / 50g;

[0019] (5) The loose packing density of the additively manufactured metal powder is 6.1 g / cm³. 3 .

[0020] A 3D printed part is produced by selective laser melting printing using additive manufacturing metal powder as described above.

[0021] In one embodiment, the 3D printed part satisfies the following conditions:

[0022] (1) The thermal conductivity is 115 W / (m·K);

[0023] (2) Hardness is 50 HRC;

[0024] (3) The density is 99.9%;

[0025] (4) The room temperature tensile strength is 1180 MPa;

[0026] (5) The elongation rate is 16%;

[0027] (6) The tensile strength is 720 MPa at a temperature of 620℃.

[0028] The additive manufacturing metal powder described in this application introduces trace amounts of Nb into the W-Ni-Cu system, optimizes the Cu content to 21.0%, and adds specific amounts of Co and Mo to form a W-Ni-Cu-Co-Mo-Nb multi-component system. Through selective laser melting (SLM) printing, a multi-synergistic strengthening mechanism of W dispersion strengthening, Nb-Mo solid solution strengthening, and Co grain boundary strengthening is constructed. This effectively improves the thermal conductivity of the alloy parts, optimizes printing adaptability, and enhances wear resistance and erosion resistance, thereby synergistically improving the overall performance of the alloy parts and significantly extending their service life. This breakthrough overcomes the technical bottleneck that existing 3D printed alloy parts cannot synergistically improve thermal conductivity, wear resistance, and printing performance. In particular, it overcomes the technical problems of poor thermal conductivity, insufficient wear resistance, and easy cracking in traditional aluminum alloy die-casting mold materials. Attached Figure Description

[0029] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1This is a 3D structural perspective view of an aluminum alloy die-casting mold according to an embodiment of this application, wherein 10 is a conformal cooling channel;

[0031] Figure 2 Metallographic diagram of the aluminum alloy die-casting mold prepared according to an embodiment of this application;

[0032] Figure 3 This is a comparison chart of the thermal conductivity of aluminum alloy die-casting molds prepared in the embodiments of this application and Comparative Examples 1 and 3. Detailed Implementation

[0033] To facilitate understanding of this application, it will be described in more detail below. However, it should be understood that this application can be implemented in many different forms and is not limited to the embodiments or examples described herein. Rather, these embodiments or examples are provided to provide a more thorough and complete understanding of the disclosure of this application.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular implementations or embodiments only and is not intended to be limiting of the application. In this application, when numerical ranges are mentioned, unless otherwise specified, such ranges are considered continuous and include the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, it includes every integer between the minimum and maximum values ​​of the range. Furthermore, when multiple ranges are provided to describe a feature or characteristic, the ranges may be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are included.

[0035] Those skilled in the art generally believe that increasing the Cu content in nickel-tungsten-copper-based alloys will reduce the high-temperature strength of the alloy. Therefore, the Cu content of conventional nickel-tungsten-copper-based alloys is usually controlled within 15%, and at most not exceeding 18%. However, the applicant has found through long-term and in-depth research that such nickel-tungsten-copper-based alloys have many problems, such as low thermal conductivity, easy cracking during SLM printing, and density below 98.5%.

[0036] Based on this, this application provides an additive manufacturing metal powder, which, by mass fraction, comprises: W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5%, and impurities, wherein the total impurity content is ≤0.5%.

[0037] The alloy phase formed by SLM printing of the additive manufacturing metal powder contains W-dispersed reinforcing particles, and the alloy grain size is 3.6 μm.

[0038] The preparation steps of the additive manufacturing metal powder are as follows:

[0039] (1) Ingredients: Select W powder, Ni powder, Cu powder, Co powder, Mo powder and Nb powder with a purity of 99.95% and a particle size of ≤8μm. Weigh them accurately according to the following ratios: W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5%, and unavoidable impurities ≤0.5%. The ingredient error is ≤±0.1%.

[0040] (2) Graded mixing: The raw material powder is placed in a high-purity argon-protected powder mixer. First, it is mixed at a low speed of 180 r / min for 2 hours, and then at a high speed of 300 r / min for 3.5 hours. The powder is cooled at a 15-minute interval in between to obtain a uniformly mixed powder.

[0041] (3) Melting and atomization: The mixed powder is added to a vacuum induction melting furnace and heated to 1580°C under the protection of high-purity argon gas. After complete melting, a uniform alloy melt is obtained. Secondary high-pressure argon gas atomization is used. The first atomization pressure is 4.0 MPa and the second atomization pressure is 5.2 MPa. The atomization temperature is 1530°C to obtain the initial powder.

[0042] (4) Sieving and drying: Two-stage sieves of 45μm and 18μm were used to screen out powder of 18μm~42μm; magnetic impurities were removed by magnetic separation, non-metallic inclusions were removed by ultrasonic cleaning, and vacuum drying was performed at 90℃ for 3h.

[0043] (5) Packaging: Place the prepared powder into a vacuum packaging bag, evacuate to 8 Pa, and seal for storage.

[0044] The additive manufacturing metal powder technology solution provided in this application introduces trace amounts of Nb into the W-Ni-Cu system, optimizes the Cu content to 21.0%, and adds specific amounts of Co and Mo to form a W-Ni-Cu-Co-Mo-Nb multi-component system. In this system, 29.0% W acts as a dispersed strengthening phase. During the rapid solidification process of SLM printing, the W particles fail to completely fuse, forming a hard second phase dispersed at the nanoscale and / or microscale. This not only differs from the carbide precipitation strengthening mechanism in conventional alloys but also significantly improves the wear resistance and resistance to molten aluminum erosion of the alloy parts. Yes; Nb and Mo synergistically improve the alloy's red hardness (the ability to maintain high hardness at high temperatures) and high-temperature strength through solid solution strengthening, overcoming the technical bias that increasing Cu content in existing nickel-tungsten-copper-based alloys leads to a decrease in high-temperature strength. At the same time, they refine the grains, precisely controlling the alloy grain size to 3.6μm, improving melt fluidity, effectively suppressing compositional segregation, reducing the sensitivity to hot cracking and thermal fatigue resistance during SLM printing, thereby effectively suppressing crack formation, improving alloy formability, and enhancing printing quality; Co further strengthens the grain boundaries, improving the alloy's creep resistance and thermal fatigue resistance in high-temperature aluminum liquid environments.

[0045] Therefore, the additive manufacturing metal powder described in this application constructs a multi-synergistic strengthening mechanism of W dispersion strengthening, Nb-Mo solid solution strengthening and Co grain boundary strengthening through selective laser melting and printing. This effectively improves the thermal conductivity of alloy parts, optimizes printing adaptability, and enhances wear resistance and erosion resistance, thereby synergistically improving the overall performance of alloy parts and significantly extending their service life. This overcomes the technical bottleneck that existing 3D printed alloy parts cannot synergistically improve thermal conductivity, wear resistance and printing performance. In particular, it overcomes the technical problems of poor thermal conductivity, insufficient wear resistance and easy cracking in traditional aluminum alloy die casting mold materials and SLM printing.

[0046] It is understandable that additive manufacturing metal powders contain unavoidable impurities, and this application does not limit the specific composition of the impurities.

[0047] In one embodiment of this application, the sphericity of the additively manufactured metal powder is preferably 97%; the oxygen content of the additively manufactured metal powder is preferably 320 ppm; in the additively manufactured metal powder, the mass of particles with a particle size of 18 μm to 30 μm is 55% of the total powder mass, which can be understood as the mass of the remaining particles with a particle size of 30 μm to 42 μm being 45% of the total powder mass; the flowability of the additively manufactured metal powder is preferably 20 s / 50 g; and the loose packing density of the additively manufactured metal powder is preferably 6.1 g / cm³. 3 .

[0048] This application optimizes parameters such as sphericity, oxygen content, particle size distribution, flowability, and loose density of additive manufacturing metal powder, which helps to ensure that the metal powder is more suitable for SLM printing process and is less prone to defects such as incomplete fusion and cracks during printing. This further improves the density of the printed parts and makes the quality of the printed parts significantly higher than that of printed parts made from existing similar alloy powders.

[0049] In one embodiment of this application, the particle size of the raw material powder is preferably ≤8μm, which is beneficial to promoting alloy uniformity, improving sphericity, and reducing particle defects.

[0050] It should be noted that optimizing the ingredient ratio to within ±0.1% is more conducive to ensuring accurate ingredient proportions.

[0051] In one embodiment of this application, the graded mixing includes: first mixing at a low speed of 180 r / min for 2 hours, cooling for 15 minutes, and then mixing at a high speed of 300 r / min for 3.5 hours, which helps to ensure the uniformity of the mixed powder composition and avoid particle agglomeration.

[0052] It is understandable that an inert gas is preferred for the environment during staged mixing, and high-purity argon with a purity greater than 99.999% is even more preferred, as it helps to protect the raw materials and avoid oxidation.

[0053] In one embodiment of this application, the gas atomization process includes: performing secondary high-pressure atomization at a temperature of 1530°C, wherein the first atomization pressure is 4.0 MPa and the second atomization pressure is 5.2 MPa. The secondary high-pressure gas flow breaks up the atomized droplets, which can efficiently prepare powder with a higher proportion of fine powder, meet the requirements of SLM printing for the proportion of fine powder, and also help to suppress element segregation, reduce compositional inhomogeneity, make the alloy structure more uniform, and thus improve the density of the printed parts.

[0054] In one embodiment of this application, the aperture of the atomizing nozzle is preferably 0.9 mm to 1.1 mm, which helps to ensure the atomization effect and obtain spherical powder with more uniform particle size.

[0055] It is understandable that an inert gas is preferred for the environment during smelting and gas atomization, and even more preferably, high-purity argon gas with a purity greater than 99.999% is preferred, as it helps to protect the alloy solution and prevent oxidation.

[0056] In one embodiment of this application, the additive manufacturing metal powder is processed by a two-stage sieving method. First, coarse powder is removed by passing the powder through a 45μm sieve, and then fine powder is removed by passing the powder through an 18μm sieve, so that powder with a particle size of 18μm to 42μm is selected.

[0057] In one embodiment of this application, the prepared additive manufacturing metal powder is placed in a vacuum packaging bag, vacuumed to a vacuum degree ≤8Pa, sealed and stored to prevent powder oxidation and ensure its performance stability.

[0058] The preparation method provided in this application is simple, highly controllable, requires no additional special equipment, is suitable for large-scale industrial production, and has controllable production costs, thus possessing high industrial application value.

[0059] This application also provides a 3D printed part, which is produced by selective laser melting printing using additive manufacturing metal powder as described above. It should be noted that this application does not limit the specific types of 3D printed parts, including but not limited to products such as aluminum alloy die-casting molds.

[0060] 3D printed parts made using the additive manufacturing metal powder provided in this application possess excellent thermal conductivity, wear resistance, and thermal fatigue resistance. They are particularly suitable for SLM printing of aluminum alloy die-casting molds, especially for the high-end aluminum alloy die-casting industry (such as automotive parts and aerospace parts die-casting). On the one hand, they can quickly dissipate the heat generated during the die-casting process, reduce mold temperature, reduce thermal stress concentration, and prevent mold cracking and deformation. At the same time, they can improve the resistance to aluminum melt erosion and extend the mold's service life. Compared with traditional H13 steel die-casting molds, the heat dissipation efficiency is more than 2 times higher, and the service life is extended by 1.8 to 2.2 times. On the other hand, they can achieve near-net-shape forming of complex structure die-casting molds without the need for extensive subsequent machining, reducing production costs and improving production efficiency. This fills the gap in the existing high-end aluminum alloy die-casting mold-specific SLM alloy powder.

[0061] In one embodiment of this application, the thermal conductivity of the 3D printed part is preferably 115 W / (m·K); the hardness of the 3D printed part is preferably 50 HRC; the density of the 3D printed part is preferably 99.9%; the room temperature tensile strength of the 3D printed part is preferably 1180 MPa; the elongation of the 3D printed part is preferably 16%; and the tensile strength of the 3D printed part at a high temperature of 620°C is preferably 720 MPa.

[0062] By adjusting the performance indicators of 3D printed parts, such as thermal conductivity, hardness, density, room temperature tensile strength, and tensile strength at 620℃, it is beneficial to ensure that 3D printed parts can adapt to the harsh working environment of aluminum alloy die casting and further extend their service life.

[0063] It is understood that this application does not impose restrictions on the specific structure of the 3D printed parts or the preparation process of laser selective melting printing. Conventional preparation processes can be used, and the structure of the parts can be designed according to specific product requirements.

[0064] In one embodiment of this application, taking an aluminum alloy die-casting mold as an example, the specific structure is as follows: Figure 1 As shown, the mold integrates conformal cooling channels 10, which fully leverages the advantages of SLM printing of complex structures. Combined with the high thermal conductivity of the additive manufacturing metal powder provided in this application, the mold can achieve rapid and uniform heat dissipation, which is conducive to further improving die casting production efficiency and product qualification rate.

[0065] In another embodiment of this application, taking an aluminum alloy die-casting mold as an example, the specific manufacturing process includes:

[0066] (1) Preparation before printing: First, take the alloy powder out of the vacuum packaging bag and put it into the powder chamber of the SLM printing equipment. Vacuum the powder chamber and printing chamber to make the vacuum degree ≤8Pa. Then, introduce high-purity argon gas (purity ≥99.999%) to make the oxygen content in the printing chamber <80ppm. After polishing and cleaning the printing substrate, preheat it to 220℃~250℃ and keep it warm for 20min~60min to eliminate the internal stress of the substrate and avoid problems such as separation of the substrate from the blank and cracking of the blank during the printing process.

[0067] (2) SLM printing: Fiber laser SLM printing equipment is used, with laser power set to 330W~390W, scanning speed to 850mm / s~1050mm / s, layer thickness to 30μm~38μm, and scanning spacing to 0.09mm~0.11mm. The scanning strategy adopts checkerboard scanning + 67° rotation. After each layer is scanned, the rotation is 67° to avoid stress concentration. High-purity argon gas is continuously introduced during the printing process for protection, maintaining the oxygen content in the printing chamber <80ppm and the temperature fluctuation ≤±5℃ to ensure the quality of the printed blank.

[0068] (3) Post-processing: The printed die-casting mold blank is peeled off from the substrate and subjected to stress-relief annealing, hot isostatic pressing and aging strengthening treatment in sequence to finally obtain the finished aluminum alloy die-casting mold. Post-processing helps to eliminate the internal stress of the printed blank and improve the density and comprehensive mechanical properties of the blank. As a preferred method: the stress-relief annealing temperature is 680℃~700℃, the holding time is 2.5h~3h, and the furnace is cooled to room temperature; the hot isostatic pressing temperature is 1180℃~1200℃, the pressure is 125MPa~130MPa, the holding time is 2h~3h, and the furnace is cooled to room temperature; the aging strengthening temperature is 720℃~750℃, the holding time is 3.5h~4h, and the air is cooled to room temperature.

[0069] The additive manufacturing metal powder, its preparation method, and its application will be further described below through specific embodiments. However, those skilled in the art will understand that the following embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used without specified manufacturers are all commercially available conventional products.

[0070] Example

[0071] The steps for preparing additive manufacturing metal powder are as follows:

[0072] (1) Ingredients: Select W powder, Ni powder, Cu powder, Co powder, Mo powder and Nb powder with a purity of 99.95% and a particle size of ≤8μm. Weigh them accurately according to the following ratios: W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5%, and unavoidable impurities ≤0.5%. The ingredient error is ≤±0.1%.

[0073] (2) Graded mixing: The raw material powder is placed in a high-purity argon-protected powder mixer. First, it is mixed at a low speed of 180 r / min for 2 hours, and then at a high speed of 300 r / min for 3.5 hours. The powder is cooled at a 15-minute interval in between to obtain a uniformly mixed powder.

[0074] (3) Melting and atomization: The mixed powder is added to a vacuum induction melting furnace and heated to 1580°C under the protection of high-purity argon gas. After complete melting, a uniform alloy melt is obtained. Secondary high-pressure argon gas atomization is used. The first atomization pressure is 4.0 MPa and the second atomization pressure is 5.2 MPa. The atomization temperature is 1530°C to obtain the initial powder.

[0075] (4) Sieving and drying: Two-stage sieves of 45μm and 18μm were used to screen out powder of 18μm~42μm; magnetic impurities were removed by magnetic separation, non-metallic inclusions were removed by ultrasonic cleaning, and vacuum drying was performed at 90℃ for 3h.

[0076] (5) Packaging: Place the prepared powder into a vacuum packaging bag, evacuate to 8 Pa, and seal for storage.

[0077] use Figure 1 The structure shown is used for SLM printing of aluminum alloy die-casting molds. The steps are as follows:

[0078] (1) Preparation before printing: Put the powder into the powder chamber of the SLM printing equipment, evacuate to 8Pa, and introduce high-purity argon gas to make the oxygen content in the printing chamber <80ppm; after polishing and cleaning the printing substrate, preheat to 235℃ and keep warm for 40min.

[0079] (2) SLM printing: laser power 360W, scanning speed 950mm / s, layer thickness 35μm, scanning spacing 0.10mm, scanning strategy is checkerboard + 67° rotation, to print the die casting mold blank;

[0080] (3) Post-processing: After peeling off the billet, stress-relief annealing at 690℃ for 2.8h, furnace cooling to room temperature; hot isostatic pressing at 1190℃ and 128MPa for 2.5h, furnace cooling; aging strengthening at 735℃ for 3.8h, air cooling to room temperature, to obtain aluminum alloy die casting mold.

[0081] Metallographic characterization was performed on the aluminum alloy die-casting molds prepared in the examples, and the results are as follows: Figure 2 As shown, the microstructure is uniform and dense, with no obvious pores, cracks and component agglomeration, and W-dispersed reinforcing particles are uniformly distributed in the nickel-copper matrix.

[0082] Comparative Example 1

[0083] The steps for preparing additive manufacturing metal powder are as follows:

[0084] (1) Ingredients: Select W powder, Ni powder, Cu powder and Co powder with a purity of 99.95% and a particle size of ≤8μm. Weigh them accurately according to W: 30.0%, Ni: 50.0%, Cu: 15.0%, Co: 5.0% and unavoidable impurities. The ingredient error is ≤±0.1%.

[0085] (2) Graded mixing: The raw material powder is placed in a high-purity argon-protected powder mixer. First, it is mixed at a low speed of 180 r / min for 2 hours, and then at a high speed of 300 r / min for 3.5 hours. The powder is cooled at a 15-minute interval in between to obtain a uniformly mixed powder.

[0086] (3) Melting and atomization: The mixed powder is added to a vacuum induction melting furnace and heated to 1580°C under the protection of high-purity argon gas. After complete melting, a uniform alloy melt is obtained. High-pressure argon gas is used for atomization at a pressure of 4.0 MPa and a temperature of 1530°C to obtain the initial powder.

[0087] (4) Sieving and drying: Two-stage sieves of 45μm and 18μm were used to screen out powder of 18μm~42μm; magnetic impurities were removed by magnetic separation.

[0088] (5) Packaging: Place the prepared powder into a vacuum packaging bag, evacuate to 8 Pa, and seal for storage.

[0089] The aluminum alloy die-casting mold was prepared using the same method as in the example.

[0090] Comparative Example 2

[0091] The difference between Comparative Example 2 and the Example is that the raw materials were weighed according to W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8% and unavoidable impurities, while the preparation method of additive manufacturing metal powder and the preparation method of aluminum alloy die casting mold were the same as those in the Example.

[0092] Comparative Example 3

[0093] An aluminum alloy die-casting mold was prepared directly using existing H13 mold steel powder, following the same method as in the example.

[0094] The additive manufacturing metal powders prepared in all examples and comparative examples were subjected to performance tests, including sphericity testing, oxygen content testing, particle size testing, flowability testing, and bulk density testing, as well as the size of reinforcing particles and gold grains. The results are shown in Table 1.

[0095] Table 1

[0096]

[0097] The performance of the aluminum alloy die-casting molds prepared in all embodiments and comparative examples was tested, including thermal conductivity, hardness, density, room temperature tensile strength, elongation, high-temperature tensile strength at 620°C, and repeated thermal shock testing (20°C~620°C). The results are as follows: Figure 3 As shown in Table 2.

[0098] Table 2

[0099]

[0100] Figure 3 The difference in thermal conductivity between the aluminum alloy die-casting molds prepared in the embodiments of this application and those prepared in Comparative Examples 1 and 3 is visually demonstrated. The thermal conductivity of the embodiments reaches 115 W / (m·K), which is much higher than that of Comparative Example 1 (75 W / (m·K)) and Comparative Example 3 (45 W / (m·K)). This fully proves that the additive manufacturing metal powder provided in this application has better thermal conductivity and can meet the high-efficiency heat dissipation requirements of aluminum alloy die-casting molds.

[0101] As shown in Table 2, the aluminum alloy die-casting molds prepared by the embodiments provided in this application have excellent thermal conductivity, no cracks, no component segregation, and a density ≥99.7%. They show no cracking after 500 thermal shocks. In particular, the aluminum melt erosion resistance of the embodiments is 2.0 times that of traditional H13 steel, and the service life is 2.0 times that of traditional H13 steel die-casting molds. They are especially suitable for high-end aluminum alloy die-casting scenarios with high wear and high heat dissipation requirements, such as automotive and aerospace fields, and are adapted to the comprehensive performance requirements of complex structures and efficient heat dissipation.

[0102] In contrast, the additive manufacturing metal powder prepared in Comparative Example 1 exhibits only W dispersion strengthening during SLM printing, lacking solid solution strengthening and grain boundary strengthening. This leads to component segregation and lack of fusion, resulting in numerous printing cracks and a significant decrease in density in the aluminum alloy die-casting mold. Its resistance to aluminum melt erosion is 1.0 times that of traditional H13 steel, and its service life is comparable to that of traditional H13 steel. However, its overall performance is far lower than that of the embodiments in this application, making it only suitable for ordinary high-temperature scenarios and unable to meet the usage requirements of high-end aluminum alloy die-casting molds.

[0103] The additive manufacturing metal powder prepared in Comparative Example 2 exhibits coarse alloy grains and numerous printing cracks during SLM printing, with generally poor thermal shock resistance and microcracks appearing after 400 cycles. Its resistance to molten aluminum erosion is 1.5 times that of traditional H13 steel, and its service life is also 1.5 times that of traditional H13 steel. However, its overall performance is significantly lower than that of the embodiments in this application, which fully demonstrates that the introduction of Nb element in the technical solution of this application can significantly improve overall performance. Comparative Example 2 is only suitable for low- to mid-range SLM printing of die-casting molds and its performance is insufficient.

[0104] The existing H13 mold steel powder used in Comparative Example 3 is carbide-strengthened during SLM printing, without dispersion strengthening, resulting in high brittleness and easy cracking during printing, leading to poor thermal shock performance and cracking after 200 cycles; it also has poor resistance to aluminum melt erosion, short service life, and its overall performance is far inferior to the example, further demonstrating the technical advantages of this application; Comparative Example 3 is only suitable for conventional die casting molds and cannot be adapted to complex structures and high-efficiency heat dissipation requirements.

[0105] Based on the above embodiments, comparative examples, and test data, it can be seen that this application, by introducing Nb element, optimizing the ratio of W, Ni, and Cu, and coordinating with Mo and Co for synergistic strengthening, while optimizing the preparation process and SLM printing process, achieves a comprehensive performance improvement of high thermal conductivity, high wear resistance, and easy printing, solving the core pain points of the prior art, meeting the usage requirements of high-end aluminum alloy die-casting molds, and having extremely high industrial application value.

[0106] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0107] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these all fall within the protection scope of this application. Therefore, the protection scope of this patent application should be determined by the appended claims.

Claims

1. An additively manufactured metal powder, characterized in that, The additive manufacturing metal powder comprises, by mass fraction: W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5%, and impurities, wherein the total impurity content is ≤0.5%. The alloy phase formed by selective laser melting and printing of the additive manufacturing metal powder contains W-dispersed reinforcing particles, and the alloy grain size is 3.6 μm. The preparation steps of the additive manufacturing metal powder are as follows: (1) Ingredients: Select W powder, Ni powder, Cu powder, Co powder, Mo powder and Nb powder with a purity of 99.95% and a particle size of ≤8μm. Weigh them accurately according to the following ratios: W: 29.0%, Ni: 44.0%, Cu: 21.0%, Co: 4.5%, Mo: 0.8%, Nb: 0.5%, and unavoidable impurities ≤0.5%. The ingredient error is ≤±0.1%. (2) Graded mixing: The raw material powder is placed in a high-purity argon-protected powder mixer. First, it is mixed at a low speed of 180 r / min for 2 hours, and then at a high speed of 300 r / min for 3.5 hours. The powder is cooled at a 15-minute interval in between to obtain a uniformly mixed powder. (3) Melting and atomization: The mixed powder is added to a vacuum induction melting furnace and heated to 1580°C under the protection of high-purity argon gas. After complete melting, a uniform alloy melt is obtained. Secondary high-pressure argon gas atomization is used. The first atomization pressure is 4.0 MPa and the second atomization pressure is 5.2 MPa. The atomization temperature is 1530°C to obtain the initial powder. (4) Sieving and drying: Two-stage sieves of 45μm and 18μm were used to screen out powder of 18μm~42μm; magnetic impurities were removed by magnetic separation, non-metallic inclusions were removed by ultrasonic cleaning, and vacuum drying was performed at 90℃ for 3h. (5) Packaging: Place the prepared powder into a vacuum packaging bag, evacuate to 8 Pa, and seal for storage.

2. The additive manufacturing metal powder according to claim 1, characterized in that, The additively manufactured metal powder meets the following conditions: (1) The sphericity of the additively manufactured metal powder is 97%; (2) The oxygen content of the additive manufacturing metal powder is 320 ppm; (3) In the additive manufacturing metal powder, the mass of particles with a particle size of 18μm~30μm accounts for 55% of the total mass of the powder; (4) The flowability of the additively manufactured metal powder is 20s / 50g; (5) The loose packing density of the additively manufactured metal powder is 6.1 g / cm³. 3 .

3. A 3D printed part, characterized in that, The metal powder is produced by selective laser melting printing using additive manufacturing powder as described in claim 1 or claim 2.

4. The 3D printed part according to claim 3, characterized in that, The 3D printed part meets the following conditions: (1) The thermal conductivity is 115 W / (m·K); (2) Hardness is 50 HRC; (3) The density is 99.9%; (4) The room temperature tensile strength is 1180 MPa; (5) The elongation rate is 16%; (6) The tensile strength is 720 MPa at a temperature of 620℃.

Citation Information

Patent Citations

  • High-copper W-Ni-Cu alloy material and preparation method thereof

    CN107988543A

  • Heat treatment method for Ni-based alloy laminate molded body, manufacturing method for Ni-based alloy laminate molded body, Ni-based alloy powder for laminate molded body, and Ni-based alloy laminate molded body

    CN110462073A